A Combined H2/Sliding Mode Controller Design for a TORA System - Ali, Hazem I.; Kadhim, Mustafa J. (Al-Nahrain Journal for Engineering Sciences, 2018)
In this work, the control of Translational Oscillations with a Rotational Actuator (TORA) system is presented in this paper. The optimal sliding mode controller is proposed to control the two DOF underactuated mechanical system. The nonlinear coupling from the rotational to the translational motion is the main problem that faces the controller design. The H2 sliding mode controller is designed to give a better performance if only sliding mode control is used. The results illustrate that the proposed H2 sliding mode controller can achieve the stabilization of the system with the variation in system parameters and disturbance.